Leadership Traits And Their Effects On Employees - Shehzad, Mohsin; Anjum, Abu Bakar; Furqan, Muhammad (Advances in Social Sciences Research Journal, 2019)
The topic we selected is how leader, leadership qualities influence the employees performance. Leadership qualities were discussed at length in this research, what qualities are important and significant for leaders succeed in respect of employee performance in an organization. How leader of past and present differs? How this relation effects the organization because this relation can either make or break an organization. How leaders who own qualities are different from those who don’t? This relation is of great importance because organizations success depends upon it. Organizations of today’s world are going leaps and bounds in doing this research. It is also discussed that how leader behavior influence the employees. Also, our chosen topic is of broad nature so further research can also be done on this topic. The aim of our research was to see what is the relationship between these two variables is and how it affects an organization? Suggestions after concluding our result is also given on how in our opinion what leaders must possess and how employees, if leader possesses all the right ingredients, act in response?